Evaluation of Antibacterial Effects of Silver-Coated Stainless Steel Orthodontic Brackets - Valiollah Arash; Fatemeh Keikhaee; Sayed Mahmood Rabiee; Ramazan Rajabnia; Soraya Khafri; Saeid Tavanafar (Tehran University of Medical Sciences, 2016)
Objectives: White spots and enamel demineralization around orthodontic brackets are among the most important complications resulting from orthodontic treatments. Since the antibacterial properties of metals and metallic particles have been well documented, the aim of this study was to assess the antibacterial effect of stainless steel orthodontic brackets coated with silver (Ag) particles. Materials and Methods: In this study, 40 standard metal brackets were divided into two groups of 20 cases and 20 controls. The brackets in the case group were coated with Ag particles using an electroplating method. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used to assess the adequacy of the coating process. In addition, antibacterial tests, i.e., disk diffusion and direct contact tests were performed at three, six, 24and 48 hours, and 15 and 30 days using a Streptococcus mutans strain. The results were analyzed using Student's t-test and repeated measures ANOVA. Conclusions: Brackets coated with Ag, via an electroplating method, exhibited antibacterial properties when placed in direct contact with Streptococcus mutans. This antibacterial effect persisted for 30 days after contact with the bacteria.